“Liberal” Multiculturalism - Tassara Zevallos, Vanessa (2011)
Today the phenomenon of multiculturalism is not strange to any reality, to such an extent that Western democracies have had to pause in their 2ter diary and pay attention to a pending agenda that proposes ethnocultural diversity. Therefore, this fact has In the first place, it is necessary to question whether the moral autonomy of man, from an individualistic perspective, continues to be the ultimate foundation of human rights in the Constitutional State, and this, since there are other realities such as the community, the nation, among others, which also have moral relevance and which in some situations could condition the exercise of individual autonomy. The individual or the community cannot be understood in isolation and, much less, be considered independently as the only moral entities relevant to the Law; because individual and community complement each other permanently and are projected on each other. Hence, there is a need to "develop legal instruments that enable the development of minority groups, so that their diversities do not make their members inferior to those who belong to the majority groups."